Efforts to Develop Children's Talents Through Extracurricular Activities at Nur El-Qolam Islamic Middle School Serang Banten - Sahudi, Sahudi; Nurdiyanto, Nurdiyanto (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2023)
Humans are born with potential and innate abilities that need to be developed. This research aims to describe and analyze how to develop students' interests and talents through extracurricular activities, as well as supporting and inhibiting factors in carrying out extracurricular activities. The approach taken in this research uses a qualitative approach with field study methods. Meanwhile, the data sources in this research contain two sources, namely primary and secondary. Primary includes interviews with teachers and students who take part in extracurricular activities, while secondary includes: journal articles, school documents, archives extracurricular mentoring books, and other internet media that are relevant to this research. The data collection techniques are observation, interviews, documentation, and triangulation. Meanwhile, the data analysis technique uses Miles and Huberman's theory, namely data reduction, data display, data presentation, and data verification so that the results can be interpreted accurately and precisely. The results of this research show that in developing students' interests and talents there are several things, including through extracurricular activities, including martial arts (taekwondo), futsal, harsh music, and scouts. As well as supporting factors in carrying out extracurricular activities: (students are in a dormitory environment because at the school all students are Santri so mum is on site. The inhibiting factors are still the large number of students' lack of discipline and the lack of mentors who guide students in developing their interests and talents.